(untitled) (Docentes 2.0 Journal, 2025)
Creating a research project is challenging over time since simultaneously, philosophical currents of thought are constantly changing, given the evolution of a technology that invades human development and threatens to replace the individual with a computer, which facilitates work. The purpose of the research was to Design the Evaluation Rubric for Non-Written Instruments Supported by Information and Communication Technologies (ICT) in a career Based on a Competence Approach, specifically for the course of Sampling Techniques and Basic Statistics, to determine the resources and means necessary to evaluate knowledge and skills with the appropriate means. From the methodological point of view, it was framed within the positivist paradigm, with a quantitative approach of non-experimental descriptive design. The population consulted was fifteen professors of the career, who answered a survey as a support element to achieve the objectives, framing the development of the work in a phase scheme. Using the documentary review, the results of the questionnaire, and the evaluation of the program, the elements that the rubric should contain were determined, ending with its development and indicating how it should be implemented.